Analysis of the tactical behavior in soccer players of different age levels - Américo, Henrique Bueno; Cardoso, Felippe Leite; Machado, Guilherme Figueiredo; Cabral, Marcelo Odilon; Resende, Elton Ribeiro; Costa, Israel Teoldo (Journal of Physical Education (Maringá), 2016)
The aim of this study was to compare the efficiency of tactical behavior between soccer players across different age levels. The sample was comprised of 400 players divided into four age groups (Under-11, -13, -15, and -17), which performed 23,855 tactical actions. To assess the tactical behavior efficiency of players was used the FUT-SAT. For statistical treatment descriptive analysis was performed. The tests Kolmogorov-Smirnov, Kruskal-Wallis, Mann-Whitney were conducted, and the level of significance of p<0,05 was adopted. The results indicated that the efficiency of tactical behavior tends to increase over time, except for the U-15 category that has a sharp drop in relation to the others. It is concluded that the efficiency of tactical behavior of the players in soccer show differences across different age levels.